Teprotumumab as a Breakthrough in Thyroid Eye Disease Therapy: A Comprehensive Review - Mesyasz, Marceli; Piszka, Mateusz; Kwapień, Eliza; Dacyl, Hubert; Owczarska, Aleksandra; Żerdka, Julia; Brasse, Patryk; Banach, Jan; Bartkowski, Jakub; Czarnecki, Filip (Quality in Sport, 2026)
Background. Thyroid Eye Disease (TED) is a complex autoimmune condition associated with Graves’ disease, causing disfigurement, visual impairment, and reduced quality of life. For decades, options were limited to non-specific anti-inflammatory treatments like glucocorticosteroids and radiotherapy, often failing to address symptoms like proptosis and diplopia. Identifying the insulin-like growth factor-1 receptor (IGF-1R) as a driver of TED pathophysiology led to targeted therapies. Aim. This study reviews teprotumumab as a breakthrough TED therapy, analyzing its mechanism, efficacy, and place in treatment algorithms relative to traditional methods. Material and methods A literature review was conducted using databases (PubMed, Embase, ClinicalTrials.gov) for articles up to November 2025. Analysis prioritized pivotal trials (OPTIC, OPTIC-X), meta-analyses, and reviews focusing on TED pathophysiology and IGF-1R inhibition. Results. TED pathogenesis involves crosstalk between TSHR and IGF-1R on orbital fibroblasts, triggering inflammation and adipogenesis. While traditional treatments offer limited relief with side effects, teprotumumab, the first FDA-approved IGF-1R inhibitor, targets these mechanisms. Clinical data shows superior efficacy in reducing proptosis and improving diplopia compared to palliative care. Conclusions. Teprotumumab is a breakthrough in TED management, shifting from symptomatic to targeted disease modification. By addressing orbital remodeling causes, it offers distinct advantages over traditional therapies, fulfilling a major unmet need.